Integrating Character Education into Religious Practices: The Management of Jumat Berkah and Bhakti Sosial Programs - Fitria, Aliva; Rodliyah, St.; Fauzi, Imron (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2025)
This study explores the optimization of the Jumat Berkah (Blessed Friday) and Bhakti Sosial (Social Service) programs as strategic initiatives for managing religious activities at SMP Al Furqon Jember (Junior High School). Recognizing that religious activities should serve not only as rituals but also as transformative and educational efforts in character development, the research adopts a qualitative case study design. Data were gathered through in-depth interviews, participant observation, and document analysis, and examined using the interactive model of Miles, Huberman, and Saldaña. The findings demonstrate that program implementation follows three strategic stages: value-oriented planning, participatory execution, and reflective evaluation. These programs actively engage students in each phase, cultivating empathy, social responsibility, and spiritual consciousness. The novelty of this study lies in its development of a contextual, collaborative, and reflective model of religious activity management, which integrates character education into religious practice through experiential learning. Departing from traditional top-down and ceremonial approaches, this model positions students as central agents of value internalization and transformation. The study affirms that the Jumat Berkah and Bhakti Sosial programs function as a living curriculum—merging spirituality, character formation, and educational management into a cohesive and sustainable framework.